O Colégio Nossa Senhora da Glória e o processo de escolarização no município de Francisco Beltrão-PR (1951-1982) - Belliato, Moacir da Costa (2017)
The purpose of this research was to study the Nossa Senhora da Glória College and its influence in the creation of teacher training courses, as well as in the establishment of normal and parish schools in Francisco Beltrão-Pr and region, contributing to the schooling process in the municipality in years from 1951 to 1982. Faced with this objective, the problem arose: In what situation was education in Francisco Beltrão at that time? Have school nuns, in partnership with municipal, state or federal agencies, built more schools in the region? The objective of the research was to understand the contribution of the school nuns of Nossa Senhora from the Glória College in the process of schooling in the municipality and the region during her career, articulated to the economic, political, religious and social issues of the period. The beginning of the cut was 1951 because it was the year of the first contact with the region and has agreed to build a house and College in Francisco Beltrão. The final cut was 1982 because it represents an autonomy and identity of the Gloria College. The idea was to recover part of this history that began in the region of Bavaria - Germany and continued in Brazil from 1937, starting in the interior of São Paulo and reaching Francisco Beltrão in 1951. We adopted as support the dialectical method to be able to understand the historical process of schooling in the municipality. In order to answer the problematized questions, we investigated the educational legislation, bibliographic sources, chronicles, documents, photographs, newspapers and magazines, as well as oral testimonies and interviews, among others. The bibliography and the set of sources made possible the understanding of the history of the institution, placing it in a more comprehensive context. The result of the study was that nuns made an important contribution to municipal and regional education. When they arrived here, they installed the Nossa Senhora da Glória Institute in makeshift rooms. Then they opened the first kindergarten in the municipality. Soon after, they built the Nossa Senhora da Glória College in CANGO, in partnership with the Federal and State Governments and with the help of the community. They encouraged the installation of two Normal Schools. One of them worked for the training of regent teachers. The other trained teachers to work in primary education. Glória College also functioned as an epicenter, contributing directly to the installation of three parochial schools in the region.